Role of Marketing Dexterity in Strategic Niche Work Life Quality Mediating Variable - أحمد محمد رضا عبد الرسول; تيسير معلا الوكيل; احمد عبد الله امانة; سرمد عبد الله امانة; ثراء ليث محمد رضا; أحمد صبيح لفتة (Iraqi Journal for Administrative Sciences, 2024)
The research aimed to explore the role of marketing Dexterity in strategic positioning, as well as whether the mediating role of quality of work life enhances that role? The importance of the research emerged through the possibility of addressing the administrative problems that Iraqi sports club departments. The sports clubs affiliated with the Ministry of Youth and Sports were chosen as an applied field for research, through the distribution of a questionnaire that included (180) respondents from the administrative and training staff of the directorates affiliated with the Ministry, as well as the boards of directors of those clubs. One of the most important results reached is the effectiveness of the mediating role of the quality of work life in enhancing the role of marketing Dexterity in the strategic position from the point of view of the sample members.